Seroprevalence of Borrelia burgdorferi sensu lato antibodies in English adult blood donors: A nationwide cross-sectional study, 2021–2022 - Eilish Hart; John Tulloch; Daniel Bailey; Tim Brooks; Heli Harvala; Peter Simmonds; Roberto Vivancos; Neil French; Amanda Semper (Ticks and Tick-Borne Diseases)
Background: Estimates of Lyme disease incidence in England are based on reporting of cases with a laboratory-confirmed diagnosis only, underestimating total cases. In 2017 - 2018, two independent reviews commissioned by the UK Government highlighted the lack of official data on Lyme disease prevalence and incidence as a critical knowledge gap. Aim: To estimate the prevalence of IgG antibodies in the English adult population specific for Borrelia burgdorferi sensu lato (Bbsl), the causative agent of Lyme disease. Methods: The prevalence of Bbsl-specific antibodies in the English population was estimated in a cross-sectional cohort, selected from an archive of residual NHS blood donor plasma samples (age range 17 - 84, collected between 2021 - 2022). 10,000 samples were randomly selected proportionate to the population size of each of the nine English administrative regions. 9,994 samples were tested using a standard two-tiered testing strategy, with an IgG/IgM ELISA followed by an IgG immunoblot (array) test for any sera with positive or indeterminate reactivity in the ELISA. Results: Out of the 9,994 samples tested, 482 were seroreactive by screening ELISA. After two-tier testing, 49 were confirmed positive. Regional and demographic differences in seroprevalence were observed after two-tier testing, but due to the low overall seroprevalence, were not significant upon multivariable analysis. Conclusion: The seroprevalence of Borrelia burgdorferi sensu lato-specific IgG in the English adult population (2021 - 2022), determined using two-tier testing was estimated at 0.49 % (95 % CI 0.36 – 0.65). This is lower than neighbouring UK nation Scotland and other northern European countries.